The Potential for EBV Vaccines to Prevent Multiple Sclerosis - Maple, Peter A.; Ascherio, Alberto; Cohen, Jeffrey I.; Cutter, Gary; Giovannoni, Gavin; Shannon-Lowe, Claire; Tanasescu, Radu; Gran, Bruno (Frontiers in Neurology, 2022)
There is increasing evidence suggesting that Epstein-Barr virus infection is a causative factor of multiple sclerosis (MS). Epstein-Barr virus (EBV) is a human herpesvirus, Human Gammaherpesvirus 4. EBV infection shows two peaks: firstly, during early childhood and, secondly during the teenage years. Approximately, 90-95% of adults have been infected with EBV and for many this will have been a subclinical event. EBV infection can be associated with significant morbidity and mortality; for example, primary infection in older children or adults is the leading cause of infectious mononucleosis (IM). A disrupted immune response either iatrogenically induced or through genetic defects can result in lymphoproliferative disease. Finally, EBV is oncogenic and is associated with several malignancies. For these reasons, vaccination to prevent the damaging aspects of EBV infection is an attractive intervention. No EBV vaccines have been licensed and the prophylactic vaccine furthest along in clinical trials contains the major virus glycoprotein gp350. In a phase 2 study, the vaccine reduced the rate of IM by 78% but did not prevent EBV infection. An EBV vaccine to prevent IM in adolescence or young adulthood is the most likely population-based vaccine strategy to be tested and adopted. National registry studies will need to be done to track the incidence of MS in EBV-vaccinated and unvaccinated people to see an effect of the vaccine on MS. Assessment of vaccine efficacy with MS being a delayed consequence of EBV infection with the average age of onset being approximately 30 years of age represents multiple challenges.